Development of Novel d‐Cycloserine Tablet with Improvement of Drug Stability and Dissolution‐Equivalence to the d‐Cycloserine‐Loaded Commercial Hard Capsule. (24th June 2020) - Kim, Jung Suk; Choi, Yoo Jin; Woo, Mi Ran; Kim, Kyeong Soo; Jin, Sung Giu; Choi, Han‐Gon
Abstract : The purpose of this study was to develop a novel d ‐cycloserine tablet with improved stability and dissolution equivalent to the d ‐cycloserine‐loaded commercial hard capsule. The effect of alkalizing agents on the d ‐cycloserine was investigated. Numerous d ‐cycloserine tablets were prepared with various calcium hydroxide contents, using direct or wet granulation compression, and their stability and dissolution were assessed compared to the commercial d ‐cycloserine‐loaded hard capsule. Long‐term stability of the selected d ‐cycloserine tablet in aluminum polyvinylchloride blister were conducted at 25 °C/60% RH or 40 °C/75% RH for 6 months. Amongst the stabilizers tested, calcium hydroxide gave the best stability at 60 °C/75% RH for 2 days due to its alkaline and waterproofing properties. Calcium hydroxide hardly affected dissolution of drug from the tablets but considerably increased stability of drug in the tablets. Particularly, the tablet prepared with d ‐cycloserine, calcium hydroxide, polyvinylpyrrolidone, and talc in the weight ratio of 250/250/40/7.5 using direct compression gave similar dissolution but significantly improved stability compared to the commercial hard capsule. This tablet, packaged in aluminum polyvinylchloride blister, was stable in the above accelerated conditions for 6 months. Therefore, this novel d ‐cycloserine tablet with enhanced stability and dissolution equivalent to the commercial hard capsule would be recommended as an alternative.